Citazioni e autocitazioni nel “Mastro-don Gesualdo” - Gian Paolo Marchi (Parole Rubate, 2015)
This essay focuses on the use of autocitation in Giovanni Verga’s Mastro-don Gesualdo (1889) and analyses echoes of characters and scenes already outlined by the writer in Novelle rusticane (specifically, I galantuomini, Il reverendo, Pane nero, La roba) and in the novel Il marito di Elena. The second section of the article claims that in the short story La roba one might find allusions to Nicholaï Gogol’s Dead Souls. Finally, I argue for possible echoes of The Betrothed, as well as Tolstoj’s short story The Death of Ivan Il’ic, in Verga’s novel.